Corrigendum to “Lead exposure and source attribution for a mammalian scavenger before and after a culling program” [Sci. Total Environ. 940 (2024) 173686] - Evie M. Jones; Myra E. Finkelstein; Amelia J. Koch; James M. Pay; Menna E. Jones; Rodrigo K. Hamede; Jordan O. Hampton (Science of The Total Environment, 2024)

Adaptive potential in the face of a transmissible cancer in Tasmanian devils - Kasha Strickland; Menna E. Jones; Andrew Storfer; Rodrigo K. Hamede; Paul A. Hohenlohe; Mark J. Margres; Hamish I. McCallum; Sebastien Comte; Shelly Lachish; Loeske E. B. Kruuk (Molecular Ecology, 2024)
Emerging infectious diseases (EIDs) not only cause catastrophic declines in wildlife populations but also generate selective pressures that may result in rapid evolutionary responses. One such EID is devil facial tumour disease (DFTD) in the Tasmanian devil. DFTD is almost always fatal and has reduced the average lifespan of individuals by around 2 years, likely causing strong selection for traits that reduce susceptibility to the disease, but population decline has also left Tasmanian devils vulnerable to inbreeding depression. We analysed 22 years of data from an ongoing study of a population of Tasmanian devils on Freycinet Peninsula, Tasmania, to (1) identify whether DFTD may be causing selection on body size, by estimating phenotypic and genetic correlations between DFTD and size traits, (2) estimate the additive genetic variance of susceptibility to DFTD, and (3) investigate whether size traits or susceptibility to DFTD were under inbreeding depression. We found a positive phenotypic relationship between head width and susceptibility to DFTD, but this was not underpinned by a genetic correlation. Conversely, we found a negative phenotypic relationship between body weight and susceptibility to DFTD, and there was evidence for a negative genetic correlation between susceptibility to DFTD and body weight. There was additive genetic variance in susceptibility to DFTD, head width and body weight, but there was no evidence for inbreeding depression in any of these traits. These results suggest that Tasmanian devils have the potential to respond adaptively to DFTD, although the realised evolutionary response will critically further depend on the evolution of DFTD itself.

Lead exposure and source attribution for a mammalian scavenger before and after a culling program - Evie M. Jones; Amelia J. Koch; James M. Pay; Menna E. Jones; Rodrigo K. Hamede; Jordan O. Hampton (Science of The Total Environment, 2024)

Human habitat modification, not apex scavenger decline, drives isotopic niche variation in a carnivore community - Olivia Bell; Menna E. Jones; Manuel Ruiz-Aravena; David G. Hamilton; Sebastien Comte; Rowena Hamer; Rodrigo K. Hamede; Jason Newton; Stuart Bearhop; Robbie A. McDonald (Oecologia, 2024)
Top carnivores can influence the structure of ecological communities, primarily through competition and predation; however, communities are also influenced by bottom-up forces such as anthropogenic habitat disturbance. Top carnivore declines will likely alter competitive dynamics within and amongst sympatric carnivore species. Increasing intraspecific competition is generally predicted to drive niche expansion and/or individual specialisation, while interspecific competition tends to constrain niches. Using stable isotope analysis of whiskers, we studied the effects of Tasmanian devil Sarcophilus harrisii declines upon the population- and individual-level isotopic niches of Tasmanian devils and sympatric spotted-tailed quolls Dasyurus maculatus subsp. maculatus. We investigated whether time since the onset of devil decline (a proxy for severity of decline) and landscape characteristics affected the isotopic niche breadth and overlap of devil and quoll populations. We quantified individual isotopic niche breadth for a subset of Tasmanian devils and spotted-tailed quolls and assessed whether between-site population niche variation was driven by individual-level specialisation. Tasmanian devils and spotted-tailed quolls demonstrated smaller population-level isotopic niche breadths with increasing human-modified habitat, while time since the onset of devil decline had no effect on population-level niche breadth or interspecific niche overlap. Individual isotopic niche breadths of Tasmanian devils and spotted-tailed quolls were narrower in human-modified landscapes, likely driving population isotopic niche contraction, however, the degree of individuals’ specialisation relative to one another remained constant. Our results suggest that across varied landscapes, mammalian carnivore niches can be more sensitive to the bottom-up forces of anthropogenic habitat disturbance than to the top-down effects of top carnivore decline.

What drives the abundance of marsupial carnivores in production forest landscapes? - Evie M. Jones; Amelia J. Koch; Dydee F. Mann; Rodrigo K. Hamede; Menna E. Jones (Forest Ecology and Management, 2023)

Transmissible cancer and longitudinal telomere dynamics in Tasmanian devils ( Sarcophilus harrisii ) - Thomas Madsen; Marcel Klaassen; Nynke Raven; Antoine M. Dujon; Geordie Jennings; Frédéric Thomas; Rodrigo Hamede; Beata Ujvari (Molecular Ecology, 2022)
A plethora of intrinsic and environmental factors have been shown to influence the length of telomeres, the protector of chromosome ends. Despite the growing interest in infection–telomere interactions, there is very limited knowledge on how transmissible cancers influence telomere maintenance. An emblematic example of transmissible cancer occurs in the Tasmanian devil ( Sarcophilus harrisii ), whose populations have been dramatically reduced by infectious cancer cells. To investigate associations between telomere dynamics and the transmissible cancer, we used longitudinal data from a Tasmanian devil population that has been exposed to the disease for over 15 years. We detected substantial temporal variation in individual telomere length (TL), and a positive significant association between TL and age, as well as a marginally significant trend for devils with devil facial tumour disease (DFTD) having longer telomeres. A proportional hazard analysis yielded no significant effect of TL on the development of DFTD. Like previous studies, we show the complexity that TL dynamics may exhibit across the lifetime of organisms. Our work highlights the importance of long‐term longitudinal sampling for understanding the effects of wildlife diseases on TL.

Transmissible cancer influences immune gene expression in an endangered marsupial, the Tasmanian devil ( Sarcophilus harrisii ) - Nynke Raven; Marcel Klaassen; Thomas Madsen; Frédéric Thomas; Rodrigo K. Hamede; Beata Ujvari (Molecular Ecology, 2022)
Understanding the effects of wildlife diseases on populations requires insight into local environmental conditions, host defence mechanisms, host life‐history trade‐offs, pathogen population dynamics, and their interactions. The survival of Tasmanian devils ( Sarcophilus harrisii ) is challenged by a novel, fitness limiting pathogen, Tasmanian devil facial tumour disease (DFTD), a clonally transmissible, contagious cancer. In order to understand the devils’ capacity to respond to DFTD, it is crucial to gain information on factors influencing the devils’ immune system. By using RT‐qPCR, we investigated how DFTD infection in association with intrinsic (sex and age) and environmental (season) factors influences the expression of 10 immune genes in Tasmanian devil blood. Our study showed that the expression of immune genes (both innate and adaptive) differed across seasons, a pattern that was altered when infected with DFTD. The expression of immunogbulins IgE and IgM:IgG showed downregulation in colder months in DFTD infected animals. We also observed strong positive association between the expression of an innate immune gene, CD16, and DFTD infection. Our results demonstrate that sampling across seasons, age groups and environmental conditions are beneficial when deciphering the complex ecoevolutionary interactions of not only conventional host‐parasite systems, but also of host and diseases with high mortality rates, such as transmissible cancers.

Quantifying 25 years of disease‐caused declines in Tasmanian devil populations: host density drives spatial pathogen spread - Calum X. Cunningham; Sebastien Comte; Hamish McCallum; David G. Hamilton; Rodrigo Hamede; Andrew Storfer; Tracey Hollings; Manuel Ruiz‐Aravena; Douglas H. Kerlin; Barry W. Brook; Greg Hocking; Manna E. Jones (Ecology Letters, 2021)
Infectious diseases are strong drivers of wildlife population dynamics, however, empirical analyses from the early stages of pathogen emergence are rare. Tasmanian devil facial tumour disease (DFTD), discovered in 1996, provides the opportunity to study an epizootic from its inception. We use a pattern‐oriented diffusion simulation to model the spatial spread of DFTD across the species' range and quantify population effects by jointly modelling multiple streams of data spanning 35 years. We estimate the wild devil population peaked at 53 000 in 1996, less than half of previous estimates. DFTD spread rapidly through high‐density areas, with spread velocity slowing in areas of low host densities. By 2020, DFTD occupied >90% of the species' range, causing 82% declines in local densities and reducing the total population to 16 900. Encouragingly, our model forecasts the population decline should level‐off within the next decade, supporting conservation management focused on facilitating evolution of resistance and tolerance.

Darwin, the devil, and the management of transmissible cancers - Rodrigo Hamede; Thomas Madsen; Hamish McCallum; Andrew Storfer; Paul A. Hohenlohe; Hannah Siddle; Jim Kaufman; Mathieu Giraudeau; Menna Jones; Frédéric Thomas; Beata Ujvari (Conservation Biology, 2021)

Comparative landscape genetics reveals differential effects of environment on host and pathogen genetic structure in Tasmanian devils ( Sarcophilus harrisii ) and their transmissible tumour - Christopher P. Kozakiewicz; Lauren Ricci; Austin H. Patton; Amanda R. Stahlke; Sarah A. Hendricks; Mark J. Margres; Manuel Ruiz‐Aravena; David G. Hamilton; Rodrigo Hamede; Hamish McCallum; Menna E. Jones; Paul A. Hohenlohe; et al. (Molecular Ecology, 2020)
Genetic structure in host species is often used to predict disease spread. However, host and pathogen genetic variation may be incongruent. Understanding landscape factors that have either concordant or divergent influence on host and pathogen genetic structure is crucial for wildlife disease management. Devil facial tumour disease (DFTD) was first observed in 1996 and has spread throughout almost the entire Tasmanian devil geographic range, causing dramatic population declines. Whereas DFTD is predominantly spread via biting among adults, devils typically disperse as juveniles, which experience low DFTD prevalence. Thus, we predicted little association between devil and tumour population structure and that environmental factors influencing gene flow differ between devils and tumours. We employed a comparative landscape genetics framework to test the influence of environmental factors on patterns of isolation by resistance (IBR) and isolation by environment (IBE) in devils and DFTD. Although we found evidence for broad‐scale costructuring between devils and tumours, we found no relationship between host and tumour individual genetic distances. Further, the factors driving the spatial distribution of genetic variation differed for each. Devils exhibited a strong IBR pattern driven by major roads, with no evidence of IBE. By contrast, tumours showed little evidence for IBR and a weak IBE pattern with respect to elevation in one of two tumour clusters we identify herein. Our results warrant caution when inferring pathogen spread using host population genetic structure and suggest that reliance on environmental barriers to host connectivity may be ineffective for managing the spread of wildlife diseases. Our findings demonstrate the utility of comparative landscape genetics for identifying differential factors driving host dispersal and pathogen transmission.

Individual and temporal variation in pathogen load predicts long‐term impacts of an emerging infectious disease - Konstans Wells; Rodrigo K. Hamede; Menna E. Jones; Paul A. Hohenlohe; Andrew Storfer; Hamish I. McCallum (Ecology, 2019)
Emerging infectious diseases increasingly threaten wildlife populations. Most studies focus on managing short‐term epidemic properties, such as controlling early outbreaks. Predicting long‐term endemic characteristics with limited retrospective data is more challenging. We used individual‐based modeling informed by individual variation in pathogen load and transmissibility to predict long‐term impacts of a lethal, transmissible cancer on Tasmanian devil ( Sarcophilus harrisii ) populations. For this, we employed approximate Bayesian computation to identify model scenarios that best matched known epidemiological and demographic system properties derived from 10 yr of data after disease emergence, enabling us to forecast future system dynamics. We show that the dramatic devil population declines observed thus far are likely attributable to transient dynamics (initial dynamics after disease emergence). Only 21% of matching scenarios led to devil extinction within 100 yr following devil facial tumor disease ( DFTD ) introduction, whereas DFTD faded out in 57% of simulations. In the remaining 22% of simulations, disease and host coexisted for at least 100 yr, usually with long‐period oscillations. Our findings show that pathogen extirpation or host–pathogen coexistence are much more likely than the DFTD ‐induced devil extinction, with crucial management ramifications. Accounting for individual‐level disease progression and the long‐term outcome of devil– DFTD interactions at the population‐level, our findings suggest that immediate management interventions are unlikely to be necessary to ensure the persistence of Tasmanian devil populations. This is because strong population declines of devils after disease emergence do not necessarily translate into long‐term population declines at equilibria. Our modeling approach is widely applicable to other host–pathogen systems to predict disease impact beyond transient dynamics.

Conserving adaptive potential: lessons from Tasmanian devils and their transmissible cancer - Paul A. Hohenlohe; Hamish I. McCallum; Menna E. Jones; Matthew F. Lawrance; Rodrigo K. Hamede; Andrew Storfer (Conservation Genetics, 2019)

Large‐effect loci affect survival in Tasmanian devils ( Sarcophilus harrisii ) infected with a transmissible cancer - Mark J. Margres; Menna E. Jones; Brendan Epstein; Douglas H. Kerlin; Sebastien Comte; Samantha Fox; Alexandra K. Fraik; Sarah A. Hendricks; Stewart Huxtable; Shelly Lachish; Billie Lazenby; Sean M. O'Rourke; et al. (Molecular Ecology, 2018)
Identifying the genetic architecture of complex phenotypes is a central goal of modern biology, particularly for disease‐related traits. Genome‐wide association methods are a classical approach for identifying the genomic basis of variation in disease phenotypes, but such analyses are particularly challenging in natural populations due to sample size difficulties. Extensive mark–recapture data, strong linkage disequilibrium and a lethal transmissible cancer make the Tasmanian devil ( Sarcophilus harrisii ) an ideal model for such an association study. We used a RAD ‐capture approach to genotype 624 devils at ~16,000 loci and then used association analyses to assess the heritability of three cancer‐related phenotypes: infection case–control (where cases were infected devils and controls were devils that were never infected), age of first infection and survival following infection. The SNP array explained much of the phenotypic variance for female survival (>80%) and female case–control (>61%). We found that a few large‐effect SNP s explained much of the variance for female survival (~5 SNP s explained >61% of the total variance), whereas more SNP s (~56) of smaller effect explained less of the variance for female case–control (~23% of the total variance). By contrast, these same SNP s did not account for a significant proportion of phenotypic variance in males, suggesting that the genetic bases of these traits and/or selection differ across sexes. Loci involved with cell adhesion and cell‐cycle regulation underlay trait variation, suggesting that the devil immune system is rapidly evolving to recognize and potentially suppress cancer growth through these pathways. Overall, our study provided necessary data for genomics‐based conservation and management in Tasmanian devils.

Conservation implications of limited genetic diversity and population structure in Tasmanian devils (Sarcophilus harrisii) - Sarah Hendricks; Brendan Epstein; Barbara Schönfeld; Cody Wiench; Rodrigo Hamede; Menna Jones; Andrew Storfer; Paul Hohenlohe (Conservation Genetics, 2017)

Infection of the fittest: devil facial tumour disease has greatest effect on individuals with highest reproductive output - Konstans Wells; Rodrigo K. Hamede; Douglas H. Kerlin; Andrew Storfer; Paul A. Hohenlohe; Menna E. Jones; Hamish I. McCallum (Ecology Letters, 2017)
Emerging infectious diseases rarely affect all members of a population equally and determining how individuals’ susceptibility to infection is related to other components of their fitness is critical to understanding disease impacts at a population level and for predicting evolutionary trajectories. We introduce a novel state‐space model framework to investigate survival and fecundity of Tasmanian devils ( Sarcophilus harrisii ) affected by a transmissible cancer, devil facial tumour disease. We show that those devils that become host to tumours have otherwise greater fitness, with higher survival and fecundity rates prior to disease‐induced death than non‐host individuals that do not become infected, although high tumour loads lead to high mortality. Our finding that individuals with the greatest reproductive value are those most affected by the cancer demonstrates the need to quantify both survival and fecundity in context of disease progression for understanding the impact of disease on wildlife populations.

Reduced Effect of Tasmanian Devil Facial Tumor Disease at the Disease Front - RODRIGO HAMEDE; SHELLY LACHISH; KATHERINE BELOV; GREGORY WOODS; ALEXANDRE KREISS; ANNE‐MAREE PEARSE; BILLIE LAZENBY; MENNA JONES; HAMISH McCALLUM (Conservation Biology, 2012)
Pathogen‐driven declines in animal populations are increasingly regarded as a major conservation issue. The Tasmanian devil ( Sarcophilus harrisii ) is threatened with extinction by devil facial tumor disease, a unique transmissible cancer. The disease is transmitted through direct transfer of tumor cells, which is possible because the genetic diversity of Tasmanian devils is low, particularly in the major histocompatibility complex genes of the immune system. The far northwest of Tasmania now holds the last remaining disease‐free wild devil populations. The recent discovery of unique major histocompatibility complex genotypes in the northwestern region of Tasmania has raised the possibility that some animals may be resilient to the disease. We examined the differences in the epidemiology and population effects of devil facial tumor disease at 3 well‐studied affected sites in eastern Tasmania and 1 in western Tasmania (West Pencil Pine). In contrast to the 3 eastern sites, there has been no rapid increase in disease prevalence or evidence of population decline at West Pencil Pine. Moreover, this is the only onsite at which the population age structure has remained unaltered 4 years after the first detection of disease. The most plausible explanations for the substantial differences in population effects and epidemiology of the disease between eastern and western sites are geographic differences in genotypes or phenotypes of devils and functional differences between tumor strains in the 2 regions. We suggest that conservation efforts focus on identifying whether either or both these explanations are correct and then, if resistance alleles exist, to attempt to spread the resistant alleles into affected populations. Such assisted selection has rarely been attempted for the management of wildlife diseases, but it may be widely applicable.

Transmission dynamics of Tasmanian devil facial tumor disease may lead to disease‐induced extinction - Hamish McCallum; Menna Jones; Clare Hawkins; Rodrigo Hamede; Shelly Lachish; David L. Sinn; Nick Beeton; Billie Lazenby (Ecology, 2009)
Most pathogens threatening to cause extinction of a host species are maintained on one or more reservoir hosts, in addition to the species that is threatened by disease. Further, most conventional host–pathogen theory assumes that transmission is related to host density, and therefore a pathogen should become extinct before its sole host. Tasmanian devil facial tumor disease is a recently emerged infectious cancer that has led to massive population declines and grave concerns for the future persistence of this largest surviving marsupial carnivore. Here we report the results of mark–recapture studies at six sites and use these data to estimate epidemiological parameters critical to both accurately assessing the risk of extinction from this disease and effectively managing this disease threat. Three sites were monitored from before or close to the time of disease arrival, and at three others disease was well established when trapping began, in one site for at least 10 years. We found no evidence for sex‐specific differences in disease prevalence and little evidence of consistent seasonal variation in the force of infection. At all sites, the disease was maintained at high levels of prevalence (>50% in 2–3‐year‐old animals), despite causing major population declines. We also provide the first estimates of the basic reproductive rate R 0 for this disease. Using a simple age‐structured deterministic model, we show that our results are not consistent with transmission being proportional to the density of infected hosts but are consistent with frequency‐dependent transmission. This conclusion is further supported by the observation that local disease prevalence in 2–3‐year‐olds still exceeds 50% at a site where population density has been reduced by up to 90% in the past 12 years. These findings lend considerable weight to concerns that this host‐specific pathogen will cause the extinction of the Tasmanian devil. Our study highlights the importance of rapidly implementing monitoring programs to determine how transmission depends on host density and emphasizes the need for ongoing management strategies involving a disease‐free “insurance population,” along with ongoing field monitoring programs to confirm whether local population extinction occurs.

Contact networks in a wild Tasmanian devil ( Sarcophilus harrisii ) population: using social network analysis to reveal seasonal variability in social behaviour and its implications for transmission of devil facial tumour disease - Rodrigo K. Hamede; Jim Bashford; Hamish McCallum; Menna Jones (Ecology Letters, 2009)
The structure of the contact network between individuals has a profound effect on the transmission of infectious disease. Using a novel technology – proximity sensing radio collars – we described the contact network in a population of Tasmanian devils. This largest surviving marsupial carnivore is threatened by a novel infectious cancer. All devils were connected in a single giant component, which would permit disease to spread throughout the network from any single infected individual. Unlike the contact networks for many human diseases, the degree distribution was not highly aggregated. Nevertheless, the empirically derived networks differed from random networks. Contact networks differed between the mating and non‐mating seasons, with more extended male–female associations in the mating season and a greater frequency of female–female associations outside the mating season. Our results suggest that there is limited potential to control the disease by targeting highly connected age or sex classes.